Soal Matematika Model PISA Konten Change and Relationships untuk Menunjang Literasi Matematis Peserta Didik - Satiti, Wisnu Siwi; -, Iftidaiyah; Khotimah, Khusnul (Exact Papers in Compilation (EPiC), 2021)
Learning mathematics today should be more than just equipping students with understanding concepts, but it should also be used to facilitate students with the ability to apply mathematical-concepts to solve problems from everyday life. The individual's ability to apply mathematical concepts (employ to solve problems from the real world is a part of mathematics-literacy. However, based on the PISA study, a program that evaluates students’ mathematics-literacy around the world, it is known that Indonesian students’ mathematics-literacy is still low compared to students from other countries. Therefore, it is necessary to increase the use of PISA-like mathematics problems at school. PISA-like mathematics problems are built in context and content. One of them is content Change and Relationships. Several previous studies have shown that many Indonesian students have difficulties in solving PISA- like mathematics problems of change and relationships content. Therefore, in this study, we developed PISA- like mathematics problems of content change and relationships for students at SMP/MTs. The product developed is used as a mathematical activity in learning at school as an effort to support students’ mathematics literacy. This study uses the Research and Development (R&D) method with the ADDIE model. Results of this study show that the product is valid and appropriate to support students' mathematics literacy.